Validitas Media Augmented Reality Berbasis Representasi Kimia Tetrahedral dengan Indeks Validasi Aiken - Dwi Retno Sari; Sri Yamtinah; Sri Retno Dwi Ariani; Sulistyo Saputro; Elfi Susanti VH; Ari Syahidul Shidiq (Postgraduate, University of Mataram, 2022)
The development of science and technology has brought significant changes to the world of education, especially in the teaching and learning process. In the learning process, there is an interaction between teachers and students to transform their knowledge in the learning environment. To convey this knowledge, a supporting factor in learning is needed, namely learning media. This study aims to determine the feasibility of chemistry learning media in the form of augmented reality (AR) media based on chemical tetrahedral representations on thermochemical materials. This study uses quantitative research methods, with data processing and analysis using the Aiken model. The instrument used is a validation questionnaire sheet to determine the feasibility of the media. The feasibility test itself is carried out by testing 1 chemist, 1 learning media expert, 1 learning technology expert, and 6 education practitioners. The results of the validation test of the feasibility of augmented reality media get the results of Aiken's V 0.9899, ​​which means that the media is feasible to use. However, improvements still need to be made according to suggestions from the validator so that the finalized product can be used as a measuring tool that meets the criteria.